The Response of Spring Onion to complication Nutrition Combination of Ab-Mix and Fermented Cow"™s UrineIn Hydroponic Cultur - Munandar, Aris; ., Darussalam; Budi, Setia (Jurnal Sains Pertanian Equator, 2020)
This research was conducted to determine the best combination of AB-mix and fermented kosarin for growth and yield of spring onion grown hidroponic. This research was carred out in the research field of Agriculture Faculty, Tanjungpura University Pontianak which took place from February 27th, until April 19th, 2019. The method of this research was Completely Randomized Design (CRD) consisted of 5 treatments, 5 replitions, and 3 sampling units plants. The combination of inorganic nutrients and fermented cow"™s urine were A = 1 ml/l Ab Mix good plant + 90 ml/l Kosarin, B = 2 ml/l Ab Mix good plant + 70 ml/l Kosarin, C = 3 ml/l Ab Mix good plant + 50 ml/l Kosarin, D = 4 ml/l Ab Mix good plant + 30 ml/l Kosarin dan 5 = ml/l Ab Mix good plant + 10ml/l Kosarin. Variabel observations in this research were plant height, leaves of each clump, total tillers of clump, plants fresh weight, root volume, plants dried weight. On the results of this study shoured that there not found the best combination of nutrition AB-Mix goodplant and the best fermented beef urine for growth and yield spring onion. Morover this results of hydroponic onions, combination nutrients provide the same affect On a hydroponic spring onion smuth and jield.Keywords: AB-mix good plant, spring onion, hydroponic, cow"™s urine.